2019
DOI: 10.1111/cxo.12807
|View full text |Cite
|
Sign up to set email alerts
|

Choroidal detachments: what do optometrists need to know?

Abstract: Choroidal detachments occur when there is an accumulation of fluid or blood in the suprachoroidal space, a potential space situated between the choroid and the sclera. They are an uncommon ocular pathology. The most common cause of choroidal detachment is secondary to trabeculectomy; however, there are other causes such as trauma and inflammation. Clinically, choroidal detachments may vary in presentation from asymptomatic, to very poor vision, severe ocular pain, vomiting and nausea. Ocular findings associate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
21
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(21 citation statements)
references
References 95 publications
(142 reference statements)
0
21
0
Order By: Relevance
“…Studies have indicated that the permeability of microvessels is related to various inflammatory cytokines, such as IL-6, IL-8, chemokine monocyte chemoattractant protein 1 (MCP-1), and intercellular adhesion molecule-1 (ICAM-1) [30]. Inflammation could be an important cause for some idiopathic UES [31]. Kumar et al [25] applied the indocyanine green chorioangiography (ICG) findings in two cases of UES to display focal areas of late-phase choroidal hyperfluorescence, which is suggestive of choroidal hyperpermeability.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies have indicated that the permeability of microvessels is related to various inflammatory cytokines, such as IL-6, IL-8, chemokine monocyte chemoattractant protein 1 (MCP-1), and intercellular adhesion molecule-1 (ICAM-1) [30]. Inflammation could be an important cause for some idiopathic UES [31]. Kumar et al [25] applied the indocyanine green chorioangiography (ICG) findings in two cases of UES to display focal areas of late-phase choroidal hyperfluorescence, which is suggestive of choroidal hyperpermeability.…”
Section: Discussionmentioning
confidence: 99%
“…Dvorak et al [30] confirmed that VEGF can enhance microvascular hyperpermeability, which could also be a factor that causes macular edema in various retinal vascular diseases, such as branch vein occlusion. It is known that anti-VEGF can reduce the hyperpermeability of choroidal vessels [31,32]. In the course of UES, if the hyperpermeability of choroidal vessels can be reduced, the suprachoroidal fluid may also decrease.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, physiological mechanisms such as vortex vein drainage, osmotic pressure, hydrostatic forces, and scleral vessels exist to maintain balance in protein and fluid levels. 1 , 2 , 3 When this equilibrium is disrupted, the blood vessels of the choriocapillaris become enlarged and hyperpermeable causing transudate and exudate to leak into the suprachoroidal space. 1 , 2 , 3 , 4 , 5 The process is exacerbated by ciliary body thickening, decreased aqueous production, and hypotony.…”
Section: Introductionmentioning
confidence: 99%
“… 1 , 2 , 3 When this equilibrium is disrupted, the blood vessels of the choriocapillaris become enlarged and hyperpermeable causing transudate and exudate to leak into the suprachoroidal space. 1 , 2 , 3 , 4 , 5 The process is exacerbated by ciliary body thickening, decreased aqueous production, and hypotony. 3 , 4 When arteriolar and venous pressure exceed the intraocular pressure (IOP), it favors additional leakage of fluid.…”
Section: Introductionmentioning
confidence: 99%
“…Various drugs have been reported to induce angle-closure glaucoma and transient myopia [ 1 ]. Indapamide is one such drug.…”
Section: Introductionmentioning
confidence: 99%